Pengenalan Uang dan Perbankan dalam Rangka Peningkatan SDM : Pengabdian Masyarakat pada Siswa/I SMK Akbar Pekanbaru - Aswanto, Aswanto; Emkhad Arif (PT Pustaka Cendekia Publisher, 2025)
Knowledge about money and banking is undeniable how important its role is in the life of society today. Money is a common means of exchange used by society, while banking is a financial institution that collects funds and then distributes them back to the community. This community service program aims to improve the quality of Human Resources (HR) through an introduction to money and banking for SMK Akbar students. The method used in this community service activity is to deliver material (lectures), then there is a discussion session (questions and answers) and at the end of the session do practice questions. This activity is a form of learning, coaching, and motivation in improving Financial Literacy. With this community service activity, it is hoped that it can improve the knowledge of human resources.